1990
DOI: 10.1111/j.1365-2044.1990.tb14331.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled fentanyl as a method of analgesia

Abstract: SummaryA study was undgrtaken to investigate the use of fentanyl by aerosol for postoperative analgesia. Seven patients hadplacebo, six received fentanyl 100 pg and seven were given fentanyl300 pg. A Key wordsAnalgesics, narcotic; fentanyl. Aerosols.A simple method of analgesia which is rapidly effective with the minimum of complex apparatus would be useful for the postoperative patient and for self administration by those suffering severe pain at home. Such systems were developed with infusion pumps, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…They also rated their analgesia as 'none' (0), 'a little' (l), 'moderate' (2), 'almost complete' (3) or 'complete' (4). The patients had been introduced to these scales on the previous day.…”
Section: Methodsmentioning
confidence: 99%
“…They also rated their analgesia as 'none' (0), 'a little' (l), 'moderate' (2), 'almost complete' (3) or 'complete' (4). The patients had been introduced to these scales on the previous day.…”
Section: Methodsmentioning
confidence: 99%
“…74 However, there have been reported side effects related specifically to the IN or inhaled route, including a bitter, burning taste, stinging in the nose, coughing, and nasal pruritus. 65,69,75,76 While evidence suggests that PCINA is efficacious, safe, noninvasive, and easy to administer, there have been only a limited number of randomized, placebo-controlled trials evaluating this route of analgesic administration. Although further research may address these problems, some authors have suggested that IN administration of opioids for postoperative pain relief is not likely to supersede other techniques, but rather play a role in the management of acute pain in children and patients for whom IV access is difficult.…”
Section: Patient-controlled Intranasal Analgesia (Pcina)mentioning
confidence: 98%
“…Opioids may also be used in the therapy of nonmalignant pain [79]. Myths about the use of opiates have been disproven by the hospice work: morphine intolerance is uncommon; addiction or persistent mental clouding is not a problem; respiratory depression does not occur if used for analgesia; oral application is easy; other strong opioids are not necessarily better than morphine; morphine is not always the best pain therapy; and morphine is not only a drug for dying patients [93,101]. There are several forms of opioid administration which have to be considered in the individual patient [30].…”
Section: Myoclonusmentioning
confidence: 99%
“…As a last resort, intraspinal analgesic administration is a safe method [45,47]. Headache due to raised intracranial pressure is frequent in terminal neurology patients; however, there is no published therapy recommendation, such as for tumor pain [4,101]. If steroids or other antiedematous therapy is not sufficient, non-steriodal antiphlogistic drugs may be tried, as well as an opiate, titrated in dose against the effect.…”
Section: Myoclonusmentioning
confidence: 99%